Expanding Access to Finance for Small and Medium Enterprises: An Analysis of Demand and Supply Side Constraints of Nepal (The Journal of Economic Concerns, 2022)
The objective of this article is to analyze the constraints on expanding access to finance with a special reference to Small and Medium Enterprises (SMEs) in Nepal. Following explorative research design, tools like review of literature, field observations, key informant interview with Banks and Financial Institutions (BFIs), and a quick questionnaire survey with SMEs in hilly districts of Nepal were deployed to collect data for this article. The descriptive statistics showed the financing gap very clearly. The constraints of SMEs on access to finance are found in policy and operational levels on both the demand and supply sides. There is a huge scope of modern technology to reduce the constraints towards expanding access to finance for SMEs in rural areas. The major constraints area includes the policy measures, lending approach and use of technology, rate of interest, availability of collateral with SMEs, risk-mitigating measures, the position of financial literacy, stage of SMEs’ market development and their business incomes, regulatory compliances, general price level, and development of the physical infrastructures.